Comrades in Health : U.S. Health Internationalists, Abroad and at Home - Brown, Theodore M., 1942-; Birn, Anne-Emanuelle, 1964- (Book collections on Project MUSE., 2013)
This collection brings together a group of professionals and activists whose lives have been dedicated to health internationalism. By presenting a combination of historical accounts and first-hand reflections, these essays aim to draw attention to the longstanding international activities of the health left and the lessons they brought home. The involvement of these progressive U.S. health professionals is presented against the background of foreign and domestic policy, social movements, and global politics.